Experimental and natural infection of Simulium sanchezi by Mansonella ozzardi in the Middle Orinoco region of Venezuela. - Yarzábal,L; Basáñez,MG; Ramírez-Pérez,J; Ramírez,A; Botto,C; Yarzábal,A (Trans R Soc Trop Med Hyg, 1985)
Experimental and natural infections of Simulium sanchezi by Mansonella ozzardi were studied in the area of Síquita, Territorio Federal Amazonas, Venezuela. The microfilariae developed synchronously in the blackflies, reaching stage L3 in seven to eight days at temperatures between 23 degrees and 27 degrees C. Larvae in different stages of development, including infective forms, were found in 0.6% of 662 unfed wild-caught females. These results confirm that simuliids are the main vectors of M. ozzardi in the American continent.